Antibodies to S2 domain of SARS-CoV-2 spike protein in Moderna mRNA vaccinated subjects sustain antibody-dependent NK cell-mediated cell cytotoxicity against Omicron BA.1 - Balinsky, Corey A.; Jiang, Le; Jani, Vihasi; Cheng, Ying; Zhang, Zhiwen; Belinskaya, Tatyana; Qiu, Qi; Long, Tran Khanh; Schilling, Megan A.; Jenkins, Sarah A.; Corson, Karen S.; Martin, Nicholas J.; et al. (Frontiers in Immunology, 2023)
Vaccination with the primary two-dose series of SARS-CoV-2 mRNA protects against infection with the ancestral strain, and limits presentation of severe disease after re-infection by multiple variants of concern (VOC), including Omicron, despite the lack of a strong neutralizing response to these variants. We compared antibody responses in serum samples collected from mRNA-1273 (Moderna) vaccinated subjects to identify mechanisms of immune escape and cross protection. Using pseudovirus constructs containing domain-specific amino acid changes representative of Omicron BA.1, combined with domain competition and RBD-antibody depletion, we showed that RBD antibodies were primarily responsible for virus neutralization and variant escape. Antibodies to NTD played a less significant role in antibody neutralization but acted along with RBD to enhance neutralization. S2 of Omicron BA.1 had no impact on neutralization escape, suggesting it is a less critical domain for antibody neutralization; however, it was as capable as S1 at eliciting IgG3 responses and NK-cell mediated, antibody-dependent cell cytotoxicity (ADCC). Antibody neutralization and ADCC activities to RBD, NTD, and S1 were all prone to BA.1 escape. In contrast, ADCC activities to S2 resisted BA.1 escape. In conclusion, S2 antibodies showed potent ADCC function and resisted Omicron BA.1 escape, suggesting that S2 contributes to cross-protection against Omicron BA.1. In line with its conserved nature, S2 may hold promise as a vaccine target against future variants of SARS-CoV-2.